Numerical Study of Electromagnetic Loss and Heat Transfer in an Oil-Immersed Transformer. (28th September 2020) - Si, Wen-Rong; Fu, Chen-Zhao; Wu, Xu-Tao; Zhou, Xiu; Li, Xiu-Guang; Yu, Yi-Ting; Jia, Xiao-Yu; Yang, Jian
Abstract : Transformer is one of the most important pieces of equipment in power system. The insulation aging and lifespan of transformer are significantly affected by hot spot distributions of internal components inside. In the present paper, the electromagnetic losses of different components and heat transfer process in a three-phase forced oil circulation transformer (400 kVA-15 kV/400 V) are numerically studied with finite element method. The leakage magnetic flux and eddy current loss density for metal components and oil tank are carefully analyzed, and the effect of metal components' electromagnetic loss on hot spot temperature of different components and oil flow in transformer is also studied. It is found that the surface current of metal components is generated by leakage magnetic flux, and surface current density is large when leakage magnetic flux concentrates. The effect caused by relative magnetic permeability of metal components is remarkable on electromagnetic loss of metal components and oil tank, while the effect caused by relative magnetic permeability of transformer tank is relatively small. Due to the mixing of metal components on oil flow, the heat transfer of core is enhanced, its hot spot temperature is lowered, and the hot spot locations of coil and core also change. These results are meaningful for further understanding of heat transfer process in transformer and important for the optimal design of transformer.